A participatory product design process with children with autism spectrum disorder. Issue 3 (3rd July 2018) - Merter, Sevi; Hasırcı, Deniz
Abstract: This study aims to explore the ways of involving children with autism in participatory product design processes. Due to the impaired skills of children with autism, a key aspect of the process is to gain an understanding of the nature of the disorder and how these children interact with their social and material surroundings as well as their daily life problems. Considering this, a case study was conducted with children with autism, their parents and teachers, and also industrial design students in a public special education centre in İzmir, Turkey. The design task was to reconsider the conventional trampoline design with respect to the needs of the sample group and the special education centre as well as the benefits it provides. The task was based on the patterns of behaviours, actions and movement. Observations, interviews and questionnaires were carried out, as well as collaborative meetings and discussion meetings. Through the case study, the findings provided insights into conducting a participatory process with children with autism, the roles of the participants, and the interaction and communication among them. Furthermore, participants' attitude towards participatory design, the potential benefits of the design process, and innovations to benefit children with autism were explained.